Surgery versus prolonged conservative treatment for sciatica: 5-year results of a randomised controlled trial. Issue 5 (16th May 2013) - Lequin, Michiel B; Verbaan, Dagmar; Jacobs, Wilco C H; Brand, Ronald; Bouma, Gerrit J; Vandertop, William P; Peul, Wilco C
Abstract : Objective: This study describes the 5 years' results of the Sciatica trial focused on pain, disability, (un)satisfactory recovery and predictors for unsatisfactory recovery. Design: A randomised controlled trial. Setting: Nine Dutch hospitals. Participants: Five years' follow-up data from 231 of 283 patients (82%) were collected. Intervention: Early surgery or an intended 6 months of conservative treatment. Main outcome measures: Scores from Roland disability questionnaire, visual analogue scale (VAS) for leg and back pain and a Likert self-rating scale of global perceived recovery were analysed. Results: There were no significant differences between groups on the 5 years' primary outcome scores. Despite at least 6 months of conservative treatment 46% of the conservatively allocated patients were treated surgically because of severe leg pain and disability. Forty-nine (21%) patients had an unsatisfactory recovery at 5 years and the recovery pattern showed that there was a variable group of 66 patients (31%) with at least one unsatisfactory outcome at 1, 2 or 5 years of follow-up. Multivariate logistic regression showed that age (>40; OR 2.42 (95% CI 1.16 to 5.02)), severity of leg pain (VAS >70; OR 3.32 (95% CI 1.69 to 6.54)) and the Mc Gill affective score (score >3; OR 6.23 (95% CI 2.23 to 17.38)) were the only significant predictors for an unsatisfactory outcome at 5 years. Conclusions: In the long term, 8% of the patients with sciatica never showed any recovery and in at least 23%, sciatica appears to result in ongoing complaints, which fluctuate over time, irrespective of treatment. Prolonged conservative care might give patients a fair chance for pain and disability to resolve without surgery, but with the risk to receive delayed surgery after prolonged suffering of sciatica. Age above 40 years, severe leg pain at baseline and a higher affective Mc Gill pain score were predictors for unsatisfactory recovery. Trial Registry ISRCT No 26872154.